PERFORMANCE EVALUATION OF HEXACOPTER UAV (ANGRAU- PUSHPAK) SPRAYING FOR MANAGEMENT OF CHILLI THRIPS (Thrips parvispinus) - A. SAMBAIAH; L. PRASANTHI; CH MADHURI; K. PURNA CHANDRA RAO; N. KAMAKSHI; N.VENKATA LAKSHMI; K. GURAVA REDDY (The Journal of Research ANGRAU, 2023)
The study aimed at evaluating efficacy of UAV spraying in managing invasive thrips, Thrips parvispinus on chilli. The experiment was conducted at operational research project (ORP) site at Lam village of Guntur district during kharif 2022-23 with restricted randomized block design. The recommended doses of pesticides issued by Central Insecticide Board and Registration Committee(CIB&RC), GoI, New Delhi were adapted. The treatments imposed were of 100%, 75% and 50% RDP with UAV and 100% RDP with human backpack sprayer and a control plot with only water spraying with drone for asserting the efficacy of drone spraying when sprayed at low volume spraying (25 L ha-1).The first spray to control thrips was carried out 112 DAS (Days After Sowing) with a spinetoram 11.7% SC on with analysis of pre and post spraying (5 days after spraying) results showed that the bio-efficacy when sprayed with 100% RDP (T1), 75% RDP(T2), 50% RDP (T3) with drone and 100% RDP with human back pack sprayer (T4) and control(T5)reduced number of thrips per flower from 7.57 to 5.8, 7.55 to 6.40, 7.55 to 10.22, 8.05 to 8.22, 8.05 to 12.95, respectively with a percent reduction over control of 50.75, 46.19, 23.65 and 36.57, respectively. The second spray was carried out at 119 DAS with Flubendiamide 19.92% +Thiacloprid 19.92% SC. The pre and post spraying (5 days after spraying) data analysis revealed that the reduction of thrips per flower over control in T1, T2, T3, T4 and T5 to 7.37, 8.32, 12.12, 10.25 and 16.03 and the percent reduction over control in T1, T2, T3 and T4 are 52.22%, 44.88%, 24.29% and 36.78%, respectively. The third spray with Fipronil 80% WG was carried out at 126 DAS and the pre and post spraying data analysis revealed that the number of thrips per flower are 5.27, 6.47, 10.55, 8.05 and 16.83 with a percent reduction over control of 68.83, 62.34, 22.08 and 38.96, respectively. The fourth spray was carried out at 133 DAS with spirotetramat 25.31% w/w OD and the pre and post spray data analysis revealed that the number of thrips per flower are of 5.12, 5.75, 9.5, 8.5 and 18.22 in T1, T2, T3, T4 and T5 and the percent reduction over control in T1, T2, T3 and T4 are 66.59, 61.68, 40.89 and 46.92, respectively. During the four sprays, it was observed that in all treatments, there was no phytotoxicity due to these chemicals spraying and the NDVI values recorded were 0.77, 0.76, 0.64, 0.72 and 0.34, respectively in the treatments T1, T2, T3, T4 and T5. The yields recorded were found to be 58.6, 55.2, 34.5, 53.8 and 14.1 q ha-1. The incremental cost-benefit ratio (ICBR) was found to be highest (4.46) in 75% RDP spray with drone, when compared to 3.58 in 100% RDP, 2.82 in 50% RDP and 2.98 in 100%RDP with human backpack sprayer respectively. The bio-efficacy of all the chemicals revealed that 100% RDP and 75% RDP sprayed with drone are on par with each other, which offers an opportunity to reduce the dosage by25% if sprayed with drone for the same bio-efficacy with highest ICBR.